Kepuasan Pelanggan Gerai Batik Keris di tinjau dari Diferensiasi Produk, Brand Image dan Pelayanan - Nura Iudita Kartikaningtyas; Eny Kustiyah; Djumali Djumali (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to determine customer satisfaction at the Keris Batik Outlet. This type of research is quantitative descriptive. The population in this study used sample 100. Then the researchers used SPSS version 21 with quantitative analysis which included validity and reliability tests, classic assumption tests, multiple linear regression analysis, hypothesis testing with the F test and t test and the coefficient of determination. Keywords: Customer Satisfaction, Product Differentiation, Brand Image, Service.